An assessment of newspaper utilisation by students in a Nigerian University (2004)
"This paper summarises the findings on on the utilisation of newspapers by undergraduate students in Ladoke Akintola University of Technology (LAUTECH) Ogbomoso, Nigeria. The variables examined include sex, age, sources of information, fascinating columns and constraints to the utilisation of newspapers in libraries. Undergraduate students (200 – 500 level) who are actual users of the newspaper reading room and who are well acquainted with the in library were used for the study. The findings revealed that undergraduate students do read newspapers but not frequently.. Majority of the users are satisfied with the information obtained in the newspapers. A high proportion of the students feel that the newspapers provided by the library is not enough compared to the number of users. However, the Information service of the library is not effective if it does not make materials like newspapers available to users."